Answer:
relative minimum would be your awnser
7) Use distributive property
3x(4x⁴ - 5x)=3x*4x⁴- 3x*5x = 12x⁵ - 15x²
8) When you open parenthesis with minus sigh in front of it, you need change sings of the terms on opposite. Then find like terms.
(5x⁴-3x³+6x)-(3x³+11x²-8x)= 5x⁴-3x³+6x -3x³-11x²+8x =5x⁴-6x³ - 11x²+14x
9)(x-2)(3x-4)=x*3x-4x-6x+8=3x²-10x+8
10) (x+6)²=(x+6)(x+6)=x²+6x+6x+36=x²+12x+36
For (x+6)², you can also use the formula of the perfect square
(a+b)²=a²+2ab+b²
For (x+6)² =x²+2*x*6 +6²=x²+12x+36
Answer:
6, 12, 24, 48, 96, 192
Step-by-step explanation:
The first term a1 = 6 and the common ratio is 2.
So it is 6, 6*2, 6*2^2 ....
There’s no slope through (5,-4)
Answer
its
www.SenatorJanSmith.gov
www.GovernmentStudiesUniversity.edu